Decoding immunomodulatory interactions: Exploring the crosstalk between bone marrow-derived mesenchymal stem cells (BM-MSCs) out the bag and peripheral blood mononuclear cells (PBMCs) for potential in-vivo immunosuppression - Monteiro, Raquel L. (2024)
Allogeneic hematopoietic stem cell transplant is vital for haematological diseases, yet chronic complications arise as donor immune cells start attacking patient tissues. A lab barrier to studying this alloreactivity is the absence of the hematopoietic stem cell niche. Here, we employed BM-MSCs from discarded collection bags to solve this hurdle. The aim was to modulate PMBC proliferation in vitro, downregulating alloreactivity and proposing immunomodulation mechanisms. Responder PBMCs were labelled with CFSE dye, and stimulator cells irradiated. Co-cultured in a 2:1 ratio to mimic alloreactivity in MLR assays (n=3) for 6 days, with or without BM-MCs. MSC phenotype examined pre- and post-co-culture. Flow cytometry examined PBMC proliferation through CFSE histograms and assessed surface marker expression of CD45+, CD3+, CD4+, CD8+, CD19+, CD56+ and CD14+. Resazurin assays tracked metabolic activity. CFSE immunofluorescence recorded PBMC proliferation, while phase-contrast images showed PBMC-MSC physical interactions. Data is shown as mean ± standard deviation. Statistical significance assessed with Two-Way ANOVA test (p<0.05). BM-MSCs expanded successfully, maintaining ideal phenotype and function. CD44+ expression increased significantly in MSCs post-culture. CFSE expression aligned only with PBMC format, whilst phase-contrast images revealed closer alignment in co-culture. Metabolic activity showed enhanced metabolism in PBMCs/MSCs co-culture, with a 15% reduction in proliferating responder cells. March's pending immunophenotyping results will enhance understanding of the observed immunosuppression. Expanding BM-MSCs from discarded bags unravelled immunosuppression in alloreactive conditions. BM-MSCs, lacking CD44, had increased expression due to in-vitro cultivation. Reduced alloreactive PBMC proliferation by 15% highlights MSCs' immunosuppressive potential. Upcoming immunophenotyping insights will detail the immunosuppression seen.